Association of biochemical markers with COVID-19 severity in Pakistan - Iqbal , Rashid; Niazi, Muhammad Aamir Khan; Shabbir, Muhammad Usman; Raza, Umama; Saleem, Alina; Bhatti, Theophilus (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate demographics, biochemical markers and clinical features of patients suffering from coronavirus disease-2019. Method: The cross-sectional study was conducted retrospectively at the Capital Hospital, Islamabad, and the Fauji Foundation Hospital, Rawalpindi, Pakistan, from October 08, 2021 to March 01, 2022 and comprised patients of either gender with coronavirus disease-2019 diagnosed on the basis of reverse transcriptase polymerase chain reaction. Patients’ demographic, clinical and laboratory findings were obtained using patient charge sheets. Coronavirus disease-2019 was categorised as non-severe, severe and critical, according to the World Health Organisation criteria. Data was analysed using SPSS 26. Results: Of the 431 patients, 91(21.1%) were men and 340(78.9%) were women. The overall mean age was 60.75±14.45 years. Of the total, 148(34.3%) had non-severe, 190(44.1%) severe and 93(21.6%) had critical condition at the time of admission. Hypertension 307(71.2%) and diabetes mellitus 249(57.8%) were the most common comorbidities, while fever 353(81.9%), shortness of breath 339(78.7%) and cough 302(70.1%) were the most common symptoms reported. Higher age was significantly associated with coronavirus disease-2019 severity (p<0.001). Among comorbidities, chronic kidney disease (p<0.001) and cancer (p=0.046), and, among signs and symptoms, shortness of breath (p=0.002) and chest pain (p=0.021), were significantly associated with coronavirus disease-2019 severity. Serum total bilirubin, alanine aminotransferase, urea and creatinine levels had significant association with disease severity (p<0.001). Total leukocyte count, neutrophil-to-lymphocyte ratio, prothrombin time, and plasma D-Dimer levels had significant association with disease severity (p<0.001). Serum ferritin, lactate dehydrogenase and interleukin-6 levels were also significantly associated with disease severity (p<0.05). Conclusion: Assessment of biochemical markers was an excellent way to monitor disease progression in coronavirus disease-2019 patients. Key Words: COVID-19, Diabetes, Severity, Hypertension, Clinical features.